The Strategy Of The Maros KPU In An Effort To Increase Community Participation In The Election Of The Regent And Vice Regent Of Maros During The Covid-19 Pandemic - Darmawati (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine the strategy of the Maros KPU in an effort to increase public participation in the election of the Regent and Deputy Regent during the covid-19 pandemic and the factors that hinder and support the Maros KPU in increasing public participation in the election of the Regent and Deputy Regent during the COVID-19 pandemic. -19. This type of research is descriptive qualitative with the research methods used are Observation, Interview, and Documentation. Data analysis techniques are reduction, data presentation, and conclusion drawing. The results of the study can be concluded that the KPU Strategy in the Maros Regency KPU Strategy in an effort to increase public political participation in the 2020 Simultaneous Regional Elections, namely: Institutional Strengthening, Implementation of Socialization, Beginner Voter Education. The supporting factors are the availability of experienced human resources and budget availability. The obstacles are the limited space for the KPU to carry out socialization because the covid-19 pandemic has not ended, the lack of financial support for socialization because some funds are diverted for handling Covid-19, the limited space for the community to participate in the socialization activities of the KPU due to the covid-19 pandemic, the number of personnel The KPU is still limited to reaching the entire community in 14 sub-districts and 103 villages/kelurahan in Maros Regency.